The role of collective motion in the ultrafast charge transfer in van der Waals heterostructures - Han Wang (Nature Portfolio, 2016)
Ultrafast charge transfer has been observed experimentally in van der Waals heterostructures. Here, Wang et al. study theoretically the collective exciton motion at the interface. They show that the oscillations lead to charge transfer, with a rate that depends critically on the coupling and on the layer stacking.